Упростите а4a²+a-2a+2б18-y+5y-5в3c-2b3c+2b-10c²г5k²-4s^4-2k-4s²4s²+2kдp+3p-3-p-5p+5е-2q-12q-1-3q+22-3qж2mm+5m-5-3mm-4m+4зn²-2n-33-2n-2n²n-22+n

упростите 
а)4a²+(a-2)(a+2)
б)18-(y+5)(y-5)
в)(3c-2b)(3c+2b)-10c²
г)5k²-4s^4-(2k-4s²)(4s²+2k)
д)(p+3)(p-3)-(p-5)(p+5)
е)(-2q-1)(2q-1)-(3q+2)(2-3q)
ж)2m(m+5)(m-5)-3m(m-4)(m+4)
з)n²(-2n-3)(3-2n)-2n²(n-2)(2+n)

  • 4a²+(a-2)(a+2)= 4a²+a²-4=5a²-4
    18-(y+5)(y-5)=18-y²+25=-y²+43=43-y²
    (3c-2b)(3c+2b)-10c²=9c²-4b²-10c²=-c²-4b²
    5k²-4s^4-(2k-4s²)(4s²+2k)=5k²-4s^4-4k²+16s^4=k²-12s^4
    (p+3)(p-3)-(p-5)(p+5)=p²-9-p²+25=16
    (-2q-1)(2q-1)-(3q+2)(2-3q)= -4q²-4q+1-6q+9q²+4-6q=5q²-16q+5
    2m(m+5)(m-5)-3m(m-4)(m+4)=2m(m²-25)-3m(m²-16)=2m³-50m-3m³+48m=-m³-2m